Introduction. Re-orienting Himalayan Borderlands - Mélanie Vandenhelsken; Aditya Kiran Kakati; Bernardo A. Michael (South Asia Multidisciplinary Academic Journal)
This special issue critically rethinks the conceptualization of borders in the Eastern Himalayas as clearly delimited by fixed lines, arguing that they are instead dynamic zones of negotiation, resistance, and reimagining. With a regional focus on the Eastern Himalayas, comprising of Nepal, Sikkim, West Bengal, Northeast India, and the Indo-Myanmar frontier, the articles in this special issue reveal how colonial categories, intellectual constructions, legal instruments, and mapping practices produced marginalization, but also how these processes remain incomplete, continually reworked by borderland communities. The concept of borderwork is used to grasp the contribution of these communities in the production of borderlands, disrupting colonial and post-colonial territorial fixation; it highlights how borders are processes, made and remade through lived practices, contestation, memory, and alternative spatialimaginaries as much as by dominant socio-political forces. Examining conceptual frameworks such as Zomia and Highland Asia in the Eastern Himalayas, we highlight their limits as much as their significance in revealing native and pre-colonial geographies, as well as the permanent un-fixity of borderlands in this region. Together, the issue offers a decentered, historically grounded perspective on borderlands as contested spaces shaped by both territorial ambitions and local spatial imaginaries.